Public Irrigation and Well-being of Women: A Tale of Two Villages in North-east Karnataka, India. Issue 3 (December 2020) - Scaria, Suma
This article explores how public irrigation mediates the well-being of women through a study of two villages in north-east Karnataka with contrasting natures of access to irrigation. It shows that public irrigation plays an "instrumental role" in the well-being of women. Here, the well-being of women is defined in terms of four dimensions that include survival, education, health and self-awareness. The village that has access to public-funded canal irrigation exhibits relatively better performance in terms of well-being of women compared to the village with non-canal irrigation. These outcomes are explained in terms of access to irrigation and distribution of land. This micro-level study shows the need to focus on public expenditure in rural infrastructure projects, including irrigation, to mitigate gender inequities.